2020
DOI: 10.1098/rsos.200950
|View full text |Cite
|
Sign up to set email alerts
|

Higher sociability leads to lower reproductive success in female kangaroos

Abstract: In social mammals, social integration is generally assumed to improve females' reproductive success. Most species demonstrating this relationship exhibit complex forms of social bonds and interactions. However, female eastern grey kangaroos ( Macropus giganteus ) exhibit differentiated social relationships, yet do not appear to cooperate directly. It is unclear what the fitness consequences of such sociability could be in species that do not exhibit obvious forms of cooperation. Using 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 73 publications
(117 reference statements)
2
15
0
Order By: Relevance
“…Carter et al (2017) showed that cooperative vampire bats may invest in quantity of social relationships at the expense of relationship quality, yet it remains unknown what strategy performs best for this species under a volatile social environment. The same applies in the other empirical studies showing some differential investment in quantity vs. quality of social relationships (Sutcliffe & Crabbe 1963, Amato 1993, Entwisle et al 2007, Sato & Zenou 2015, Vacca 2019, Silk et al 1999, Ellis et al 2019, Morrison et al 2020, Menz et al 2020, Bond et al 2021.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Carter et al (2017) showed that cooperative vampire bats may invest in quantity of social relationships at the expense of relationship quality, yet it remains unknown what strategy performs best for this species under a volatile social environment. The same applies in the other empirical studies showing some differential investment in quantity vs. quality of social relationships (Sutcliffe & Crabbe 1963, Amato 1993, Entwisle et al 2007, Sato & Zenou 2015, Vacca 2019, Silk et al 1999, Ellis et al 2019, Morrison et al 2020, Menz et al 2020, Bond et al 2021.…”
Section: Discussionsupporting
confidence: 69%
“…Losses of individuals whose networks did not help them avoid death create a process of selective disappearance within each cohort. This makes it exceedingly hard to collect unbiased data: unless one traces social bonds longitudinally and records every death, any analysis among living individuals will pay disproportionate attention to the successful subset of individuals who are presently observable by virtue of being alive — a problem which applies to a wide range of taxa (beyond bats), whenever aiming to document effects of the quantity vs. quality of social relationships (Sutcliffe & Crabbe 1963, Amato 1993, Entwisle et al 2007, Sato & Zenou 2015, Vacca 2019, Silk et al 1999, Carter et al 2017, Ellis et al 2019, Morrison et al 2020, Menz et al 2020, Bond et al 2021). Whenever disappearance is selective (not random), the problem is exacerbated by the fact that situations where selection is at its strongest also produce the most severe data collection biases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are of course additional causes of mortality such as starvation induced by drought, competition or both [95], and disease [96]. There may also be densitydependent suppression of breeding success [97,98]. There is also non-human predation (e.g., [99]).…”
Section: Human Predation Declinementioning
confidence: 99%